“You Have to Strike That Balance Between Sharing and Charging”: Cape Breton Fiddling and Intellectual Property Rights - Hayes, Ian (Ethnologies)

(untitled) (Association Canadienne d’Ethnologie et de Folklore, 2011)
This article will discuss the concept of musical ownership and copyright in the Cape Breton fiddling tradition. Intellectual property rights have become an increasingly important issue in recent years and represent an intersection between the commercial music industry and vernacular tradition. As such, the way boundaries are constructed in regard to repertoire and ownership is subject to debate. On one hand, some discourses favor the rights of the individual, arguing that intellectual property should be protected, acknowledged and subject to financial compensation. Other perspectives favor the rights and needs of the community, valuing free exchange.